A New Sequence Which Converges Faster towards the Euler–Mascheroni Constant - Jenica Cringanu (Journal of Mathematics)
The aim of this paper is to propose a new sequence that approximates the Euler–Mascheroni constant which converges faster towards its limit and to establish new inequalities for this constant.